Cell compartmentation of ultraviolet‐absorbing compounds: An underexplored tool related to bryophyte ecology, phylogeny and evolution. (30th January 2018) - Monforte, Laura; Soriano, Gonzalo; Núñez‐Olivera, Encarnación; Martínez‐Abaigar, Javier
Abstract: Excessive exposure to ultraviolet (UV) radiation can be harmful to photosynthetic organisms, that most frequently respond with the accumulation of protective UV‐absorbing compounds (UVACs). UVACs location in different cell compartments can influence their preferential protective role as antioxidants and/or UV screens. However, the phylogenetic, ecological and evolutionary implications of UVACs compartmentation has been little studied, particularly in bryophytes. We analysed UVACs in the methanol‐soluble and ‐insoluble fractions (SUVACs and IUVACs respectively) in extracts of 87 bryophytes belonging to their three evolutionary lineages: 22 liverworts, 64 mosses and one hornwort. Assuming that the cell wall‐bound IUVACs are more effective UV screens than the mainly vacuolar SUVACs, thus conferring a higher UV tolerance, we evaluated whether UVACs levels and compartmentation were related to: (1) the bryophyte phylogeny down to the Order level; and (2) the bryophyte ecological attributes, including sun exposure and Ellenberg indicator values (numerical system classifying species' habitat along gradients of environmental factors). A similar phylogenetic and ecological analysis was conducted on the sclerophylly index (the ratio between the dry mass and the surface area of the bryophyte shoot). Mosses showed lower SUVACs but higher IUVACs and total UVACs, together with higher IUVAC/SUVAC ratios, than liverworts. Thus, mosses would better tolerate UV radiation than liverworts, which matches well with their general ecological preferences. As bryophytes were the earliest diverging land plants, we could infer that the different UVACs compartmentation between mosses and liverworts could have influenced their ecological segregation upon plant land colonization. UVACs compartmentation also differed between the two major moss lineages (acrocarpous and pleurocarpous), while the anatomically peculiar Sphagnales were the best characterized Order. There were not solid relationships between UVACs and the ecological attributes considered. Hence, UVACs might be mainly constitutive in bryophytes, depending more on the species phylogeny than on the habitat occupied in nature. Liverworts were less sclerophyllous than mosses, and, as in tracheophytes, water restrictions and high sun exposures increased sclerophylly. In conclusion, UVACs compartmentation represents an ecophysiological trait useful to understand the bryophyte ecophylogeny, because different compartmentation modalities seem to imply different UV adaptations and tolerance. Aplain language summary is available for this article. Abstract : Plain Language Summary